Development of Contextual Learning-Based E-Module in Elementary School - Juwantara, Ridho Agung; Harjanto, Ambyah; Sutiyono, Akhmad; Utari, Dwi (JIP Jurnal Ilmiah PGMI, 2023)
This research was motivated by the unavailability of contextual learning-based E-Modules in Civic lessson for Class IV Student of Insan Mandiri Elementary School at Bandar Lampung, so teaching and learning activities in class are still lacking in variety. E-Module are important for students to use because they make learning easier. A contextual approach is used to help student learn by associating learning material with the life around. The research method of this study used Development Research with the ADDIE model. Questionnaires, interviews, tests as data collection tools. This research is analyzed and explained with numbers and descriptive. Based on the results of the research, the material validation results were 83%, language validation was 93%, and design validation was 91%. The results of the teacher's response test were 78% and the student's response test was 80% in the "Decent" category. The effectiveness test obtained an average of 91 in the "Very High" effectiveness category. This research shows that the development of Civics E-Module teaching products based on contextual learning is urgently needed and deserves to be disseminated.